PEMBELAJARAN ORGANISASI PADA PONDOK PESANTREN DALAM MEMASUKI ERA GLOBAL - Zainuddin, Moh. Riza (e-Journal STAI Muhammadiyah Tulungagung, 2013)
National problems that never ended, ranging from the economicslump, a leadership crisis, a moral crisis, the environmental crisisto the threat of terrorism, requires all the elements and componentsof the nation to stand and take part as a problem solver. Noexception with a wide range of potential schools that are stillhidden treasures tub. This is one of the major challenges of ourtimes, how big the potential raises pesantren became a realcontribution to society and the nation.